Comparative efficacy of electrokinetic and static leaching for selective metal recovery and nutrient release from porphyry Cu tailings - Yujie Yan; Gawen R.T. Jenkin; Andrew P. Abbott; Alexandria Tanciongco; Carlo A. Arcilla; Cris Reven L. Gibaga; Daniel J. Smith; Djoan Kate Tungpalan; Jonathan E. Chambers; John Henry C. Gervasio; James Symons; Justine Perry T. Domingo; et al. (Chemical Engineering Journal, 2026)

Intrinsic and environmental drivers of pairwise cohesion in wild Canis social groups - John F. Benson; David A. Keiter; Peter J. Mahoney; Benjamin L. Allen; Lee Allen; Francisco Álvares; Morgan L. Anderson; Shannon M. Barber‐Meyer; Adi Barocas; James C. Beasley; Linda Behrendorff; Jerrold L. Belant; et al. (Ecology, 2025)
Animals within social groups respond to costs and benefits of sociality by adjusting the proportion of time they spend in close proximity to other individuals in the group (cohesion). Variation in cohesion between individuals, in turn, shapes important group‐level processes such as subgroup formation and fission–fusion dynamics. Although critical to animal sociality, a comprehensive understanding of the factors influencing cohesion remains a gap in our knowledge of cooperative behavior in animals. We tracked 574 individuals from six species within the genus Canis in 15 countries on four continents with GPS telemetry to estimate the time that pairs of individuals within social groups spent in close proximity and test hypotheses regarding drivers of cohesion. Pairs of social canids ( Canis spp.) varied widely in the proportion of time they spent together (5%–100%) during seasonal monitoring periods relative to both intrinsic characteristics and environmental conditions. The majority of our data came from three species of wolves (gray wolves, eastern wolves, and red wolves) and coyotes. For these species, cohesion within social groups was greatest between breeding pairs and varied seasonally as the nature of cooperative activities changed relative to annual life history patterns. Across species, wolves were more cohesive than coyotes. For wolves, pairs were less cohesive in larger groups, and when suitable, small prey was present reflecting the constraints of food resources and intragroup competition on social associations. Pair cohesion in wolves declined with increased anthropogenic modification of the landscape and greater climatic variability, underscoring challenges for conserving social top predators in a changing world. We show that pairwise cohesion in social groups varies strongly both within and across Canis species, as individuals respond to changing ecological context defined by resources, competition, and anthropogenic disturbance. Our work highlights that cohesion is a highly plastic component of animal sociality that holds significant promise for elucidating ecological and evolutionary mechanisms underlying cooperative behavior.

The mouse metabolic phenotyping center (MMPC) live consortium: an NIH resource for in vivo characterization of mouse models of diabetes and obesity - Maren Laughlin; Richard McIndoe; Sean H. Adams; Renee Araiza; Julio E. Ayala; Lucy Kennedy; Louise Lanoue; Louise Lantier; James Macy; Eann Malabanan; Owen P. McGuinness; Rachel Perry; et al. (Mammalian Genome, 2024)
The Mouse Metabolic Phenotyping Center (MMPC) Live Program was established in 2023 by the National Institute for Diabetes, Digestive and Kidney Diseases (NIDDK) at the National Institutes of Health (NIH) to advance biomedical research by providing the scientific community with standardized, high quality phenotyping services for mouse models of diabetes and obesity. Emerging as the next iteration of the MMPC Program which served the biomedical research community for 20 years (2001–2021), MMPC Live is designed as an outwardly-facing consortium of service cores that collaborate to provide reduced-cost consultation and metabolic, physiologic, and behavioral phenotyping tests on live mice for U.S. biomedical researchers. Four MMPC Live Centers located at universities around the country perform complex and often unique procedures in vivo on a fee for service basis, typically on mice shipped from the client or directly from a repository or vendor. Current areas of expertise include energy balance and body composition, insulin action and secretion, whole body carbohydrate and lipid metabolism, cardiovascular and renal function, food intake and behavior, microbiome and xenometabolism, and metabolic pathway kinetics. Additionally, an opportunity arose to reduce barriers to access and expand the diversity of the biomedical research workforce by establishing the VIBRANT Program. Directed at researchers historically underrepresented in the biomedical sciences, VIBRANT-eligible investigators have access to testing services, travel and career development awards, expert advice and experimental design consultation, and short internships to learn test technologies. Data derived from experiments run by the Centers belongs to the researchers submitting mice for testing which can be made publicly available and accessible from the MMPC Live database following publication. In addition to services, MMPC Live staff provide expertise and advice to researchers, develop and refine test protocols, engage in outreach activities, publish scientific and technical papers, and conduct educational workshops and training sessions to aid researchers in unraveling the heterogeneity of diabetes and obesity.

Sensorimotor Cough Dysfunction in Cerebellar Ataxias - Emilie R. Lowell; James C. Borders; Sarah E. Perry; Avery E. Dakin; Jordanna S. Sevitz; Sheng-Han Kuo; Michelle S. Troche (The Cerebellum, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Determining the underlying structure of insular isolation measures - Zachary T. Carter; George L. W. Perry; James C. Russell (Journal of Biogeography, 2020)
Aim Island isolation is measured in many ways. We seek to determine what the underlying latent factors characterizing these measures are, in order to understand how they mechanistically drive island biogeographical patterns and in order to recommend the most parsimonious measures. We then test the discriminatory power of the identified components against hypotheses generated from the biogeographical patterns of invasive rats. Location The 890 offshore islands (≥1 hectare area) of the New Zealand archipelago (latitude: 34.1–47.3°S, longitude: 166.2–178.4°E). Taxon Mammals. Methods We identified 16 measures that have been frequently used to characterize isolation in the past, including Euclidean‐based distance metrics, landscape connectivity metrics derived from least‐cost and circuit theory modelling, landscape buffers, stepping stones and insular area. We used principal components analysis (PCA) to synthesize the underlying structure of insular isolation with respect to terrestrial mammal dispersal. Finally, we tested the discriminatory power of retained principal components (PCs) using permutational multivariate analyses of variance (PERMANOVA). Tests include comparison of historical rat distributions, islands targeted for rat eradication and islands reinvaded by rats. Results The underlying structure of island isolation as characterized in the 16 metrics was described by three independent PCA components. Variable clustering suggests that PC1 captured distance from the mainland source to the focal island (PC1 Distance), PC2 described stepping stones available along the dispersal pathway (PC2 Stepping Stones) and PC3 described the focal island's position in the landscape (PC3 Insular Network). Each discriminatory test affirmed its respective biogeographical pattern hypothesis. Main conclusions The three underlying components we identify form the basis of a robust description of insular isolation that is of broad importance to understanding island biogeography dynamics. Moreover, these components can be applied across taxa without extensive structural or functional assumptions because the highest loading variables are not biologically informed.

Cerebrovascular haemodynamics during isometric resistance exercise with and without the Valsalva manoeuvre - Blake G. Perry; Tom De Hamel; Kate N. Thomas; Luke C. Wilson; Travis D. Gibbons; James D. Cotter (European Journal of Applied Physiology, 2020)

Advocating for Science: Amici Curiae Brief of Wetland and Water Scientists in Support of the Clean Water Rule - Royal C. Gardner; Erin Okuno; Steph Tai; M. Siobhan Fennessy; Carol A. Johnston; Marinus L. Otte; Margaret Palmer; James E. Perry; Charles Simenstad; Benjamin R. Tanner; Dan Tufford; R. Eugene Turner; et al. (Wetlands, 2019)

Carbon dioxide enrichment alters predator avoidance and sex determination but only sex is mediated by GABAA receptors - Jean-Claude Abboud; Edgar A. Bartolome; Mayra Blanco; Annalise C. Kress; Ian Y. Ellis; Perry K. Yazzolino; Kamrin I. Sorensen; James R. Winslow; David A. Cleary; Hugh Lefcort (Hydrobiologia, 2019)

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

Heart rate analysis by sparse representation for acute pain detection - Shai Tejman-Yarden; Ofer Levi; Alex Beizerov; Yisrael Parmet; Tu Nguyen; Michael Saunders; Zvia Rudich; James C. Perry; Dewleen G. Baker; Tobias Moeller-Bertram (Medical & Biological Engineering & Computing, 2016)

Computational Modeling of Pathophysiologic Responses to Exercise in Fontan Patients - Ethan Kung; James C. Perry; Christopher Davis; Francesco Migliavacca; Giancarlo Pennati; Alessandro Giardini; Tain-Yen Hsia; Alison Marsden (Annals of Biomedical Engineering, 2015)

Erratum to: Genome-wide association study (GWAS) of carbon isotope ratio (δ13C) in diverse soybean [Glycine max (L.) Merr.] genotypes - Arun Prabhu Dhanapal; Jeffery D. Ray; Shardendu K. Singh; Valerio Hoyos-Villegas; James R. Smith; Larry C. Purcell; C. Andy King; Perry B. Cregan; Qijian Song; Felix B. Fritschi (Theoretical and Applied Genetics, 2015)

CTFS ‐Forest GEO : a worldwide network monitoring forests in an era of global change - Kristina J. Anderson‐Teixeira; Stuart J. Davies; Amy C. Bennett; Erika B. Gonzalez‐Akre; Helene C. Muller‐Landau; S. Joseph Wright; Kamariah Abu Salim; Angélica M. Almeyda Zambrano; Alfonso Alonso; Jennifer L. Baltzer; Yves Basset; Norman A. Bourg; et al. (Global Change Biology, 2015)
Global change is impacting forests worldwide, threatening biodiversity and ecosystem services including climate regulation. Understanding how forests respond is critical to forest conservation and climate protection. This review describes an international network of 59 long‐term forest dynamics research sites ( CTFS ‐Forest GEO ) useful for characterizing forest responses to global change. Within very large plots (median size 25 ha), all stems ≥1 cm diameter are identified to species, mapped, and regularly recensused according to standardized protocols. CTFS ‐Forest GEO spans 25°S–61°N latitude, is generally representative of the range of bioclimatic, edaphic, and topographic conditions experienced by forests worldwide, and is the only forest monitoring network that applies a standardized protocol to each of the world's major forest biomes. Supplementary standardized measurements at subsets of the sites provide additional information on plants, animals, and ecosystem and environmental variables. CTFS ‐Forest GEO sites are experiencing multifaceted anthropogenic global change pressures including warming (average 0.61 °C), changes in precipitation (up to ±30% change), atmospheric deposition of nitrogen and sulfur compounds (up to 3.8 g N m −2 yr −1 and 3.1 g S m −2 yr −1 ), and forest fragmentation in the surrounding landscape (up to 88% reduced tree cover within 5 km). The broad suite of measurements made at CTFS ‐Forest GEO sites makes it possible to investigate the complex ways in which global change is impacting forest dynamics. Ongoing research across the CTFS ‐Forest GEO network is yielding insights into how and why the forests are changing, and continued monitoring will provide vital contributions to understanding worldwide forest diversity and dynamics in an era of global change.

Genome-wide association study (GWAS) of carbon isotope ratio (δ13C) in diverse soybean [Glycine max (L.) Merr.] genotypes - Arun Prabhu Dhanapal; Jeffery D. Ray; Shardendu K. Singh; Valerio Hoyos-Villegas; James R. Smith; Larry C. Purcell; C. Andy King; Perry B. Cregan; Qijian Song; Felix B. Fritschi (Theoretical and Applied Genetics, 2015)

High-throughput genotyping with the GoldenGate assay in the complex genome of soybean - David L. Hyten; Qijian Song; Ik-Young Choi; Mun-Sup Yoon; James E. Specht; Lakshmi K. Matukumalli; Randall L. Nelson; Randy C. Shoemaker; Nevin D. Young; Perry B. Cregan (Theoretical and Applied Genetics, 2008)

Virtual observatories for space and solar physics research - Christopher C. Harvey; Michel Gangloff; Todd King; Christopher H. Perry; D. Aaron Roberts; James R. Thieman (Earth Science Informatics, 2008)

The effects of 10 days of spaceflight on the shuttle Endeavour on predominantly fast-twitch muscles in the rat - William J. Kraemer; Robert S. Staron; Scott E. Gordon; Jeff S. Volek; L. Perry Koziris; Noel D. Duncan; Bradley C. Nindl; Ana L. Gómez; James O. Marx; Andrew C. Fry; Jerry D. Murray (Histochemistry and Cell Biology, 2000)